Białoruska gospodarka — cud gospodarczy, którego nie ma - Bodzoń, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
This article presents economical and social situation in Belarus. Moreover, it includes description of political system functioning in the country as well as indicates possible directions of further development. It was necessary to analyze political changes occuring in this area in order to provide better understanding of the situation in that region.The biggest problems are political system, government’s regime and economical dependence on Russia. For that reason it is important to help Belarus and make it independent on Russia. It is the only possibility to make it strong and free country, capable of international cooperation.
Keywords: Białoruś; gospodarka